Cosmopolitan impressions from a contemporary Bengali patachitra painting museum collection in Portugal - Inês Ponte (Ateliers d'Anthropologie)
In the contemporary work done by rural patua artisans, an Indian folk art, questions about tradition and innovation are interwoven with what I call “cosmopolitan impressions”. Focusing particularly on the recent development of women as painters and performers of the patua folk craft in an expanded market, through a study of the acquisition of a patachitra collection by the Ethnology Museum in Lisbon, I explore the cosmopolitan impressions in the work of such women from the village of Naya. I will analyse a few threads related to the conditions that lead women to become artisans of an art traditionally associated with men, and suggest that the particular attitude encountered within the patua community in Naya has enabled the more or less successful continuity of their activity up to today. First, I briefly outline their contemporary trajectories, before taking a detailed look at their views on their activity, and then I conclude with an overview of their iconographic themes. The combination of these overlapping threads provides evidence for what I call a “cosmopolitan tradition”.